Distribution Characteristics and Risk Assessment of Mercury in Sediments From Taihu Lake - Su, Hailei; Shi, Di; Yang, Jiwei; Tao, Yanru; Sun, Fuhong; Wei, Yuan (Frontiers in Environmental Science, 2021)
Persistent pollutants are easily to accumulate in sediments, which can cause toxicity to benthos and secondary pollution to water. Mercury (Hg), as one kind of bioaccumulative and persistent pollutant, could cause great harm to water ecology and health, and has been widely concerned. The distribution characteristics and ecological risk of Hg in sediments from Taihu Lake were studied. In addition, the sediment quality criteria (SQC) of Hg was derived using tissue-based toxicity data combined with phase equilibrium partitioning approach (EqP) and the ecological risk level of Hg in Taihu Lake sediment was evaluated. The results showed that Hg was detected in all the 30 sediment-samples, and the concentrations of Hg ranged from 9.7 ng/g to 237.0 ng/g, with an average of 76.3 ng/g. The SQC of Hg was calculated to be 108.9 ng/g and the ecological risk of Hg in the sediments of Taihu Lake is in the middle level, indicating that the Hg pollution need to be paid more attention. The results provide support for environmental management and risk assessment of Hg.